2018
DOI: 10.3389/fendo.2018.00585
|View full text |Cite
|
Sign up to set email alerts
|

Different Heart Rate Patterns During Cardio-Pulmonary Exercise (CPX) Testing in Individuals With Type 1 Diabetes

Abstract: To investigate the heart rate during cardio-pulmonary exercise (CPX) testing in individuals with type 1 diabetes (T1D) compared to healthy (CON) individuals. Fourteen people (seven individuals with T1D and seven CON individuals) performed a CPX test until volitional exhaustion to determine the first and second lactate turn points (LTP1 and LTP2), ventilatory thresholds (VT1 and VT2), and the heart rate turn point. For these thresholds cardio-respiratory variables and percentages of maximum heart rate, heart ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 35 publications
1
11
1
Order By: Relevance
“…In humans, the rate‐lowering effect of the HCN blocker ivabradine was correlated with the intrinsic heart rate 13 and exercise training reduces heart rate via downregulation of HCN4 14 . Collectively, these results may explain the apparent discrepancy between our results and clinical reports about decreased heart rate response in elderly people, patients with diabetes or restricted exercise capacitance 15–17 …”
Section: Discussionmentioning
confidence: 48%
“…In humans, the rate‐lowering effect of the HCN blocker ivabradine was correlated with the intrinsic heart rate 13 and exercise training reduces heart rate via downregulation of HCN4 14 . Collectively, these results may explain the apparent discrepancy between our results and clinical reports about decreased heart rate response in elderly people, patients with diabetes or restricted exercise capacitance 15–17 …”
Section: Discussionmentioning
confidence: 48%
“…Table 1 below shows low, moderate and high levels of exercise intensity can be measure through the increase of the heart rate per minute. The higher intensity of the activity being performed, the higher the heart rate [15][16][17][18]. In this research will be a focus on the high-intensity interval training activity toward the electromagnetic radiation that will emit from the human body.…”
Section: Intensity Of Exercisementioning
confidence: 99%
“…Diabetologists and diabetes patient educators (American Diabetes Association, 2019a) may also refer their athletic patients to understand glycemic responses to exercise (hypo- or hyperglycemia) or unexplained changes in performance, or simply to increase patient’s education and individual competence, which includes specific dietary and medication adaptations required for different physical activities of various intensities (American Diabetes Association, 2019a). Athletic trainers may want to use CPET to target with precision training heart rate ranges in diabetic athletes given the fact that recent research has shown systematic overestimation of target heart rate in diabetic individuals when applying computation percentages of maximum heart rate or heart rate reserve compared to objective individual markers obtained during a CPET (Moser et al, 2018b). Like with any other exercise testing, the referral purpose should be clear in advance.…”
Section: Referralmentioning
confidence: 99%
“…This is of importance for exercise prescription. Submaximal thresholds measured during CPET are valid and objective individual markers for patients with diabetes, while using percentages of maximum values, maximum heart rate, or oxygen uptake, are not sufficient to prescribe exercise intensity individually as almost 63% of their diabetic cohort presented atypical heart rate responses (Moser et al, 2018b). Thus, prescribing by percentages of maximal heart rate or heart rate range not based on individual thresholds may push individuals with diabetes to exercise at too high intensity, inducing different training effects than those desired (Moser et al, 2018b).…”
Section: Interpretation and Training Zonesmentioning
confidence: 99%